O movimento da informação fílmica: um inventário de efeitos do cinema documentário contemporâneo - Andrade, Matheus José Pessoa de (2022)
This research presents an inventory of effects resulting from the technological changes of contemporary documentary cinema. Our general objective was to verify the cultural effects arising from technological changes in the production and circulation of films, which alter the way in which film information moves and reshapes the flow of memories in social groups, which generates a transformation in social relations. From the perspective of Information Science, a rereading of the work of Herbert Marshall McLuhan was made to approach information from its theoretical perspective. By proposing a notion of medium, which involves aspects such as materiality, the user and the information environment, the author chooses the movement of information as the axis of sociocultural transformations. It is a theoretical concept constituted by the characteristics of translation and conduction of knowledge, centered on the form of information. It was applied, therefore, on the contemporary documentary, aiming at understanding the impacts of the digitalization of cinema. The McLuhanian method consists of describing, comparing and analyzing the social and cultural effects inscribed in the ways in which human associations are structured by the environment in certain contexts. The purpose is to denaturalize the communication practices naturalized within the system of interactions between people. In the case of the movement of film information, it passes through the stages of processing and circulation of films. From cameras to screens, information technology enabled a readjustment in the cinematographic sector that modified processes and flows of production and consumption of documentaries by accelerating the movement of filmic information. The documentary is seen here for its ability to mobilize audiovisual experiences through cinematographic works, considering the dynamics that these films are made and broadcast in the digital age and the experiences that constitute these forms of memory in contemporary times. Instruments such as Handycam, BitTorrent, Netflix, Youtube and Smartphone were analyzed in order, in an essay style, to make an analytical description of the effects caused by the respective technologies in documentary cinema. The thesis brings to light a series of memories inscribed in the roles played by users, values and behaviors, market niches, filming dealings, international articulations, collecting practices, modes of production and itinerant consumption, seen as effects of the changes caused by digitalization. from the movies. Finally, it is considered a work with epistemological contributions to the field of Information Science, as well as a panorama of memories about contemporary documentary, articulated from a peculiar point of view to add to the field of Cinema studies.